Relationship of lunar phases and sex of the foetus: a retrospective study - Raj, Aman Deep; Abichandani, Roshni; Sethi, Harish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The relation of lunar phases at the time of conception to the sex of the child at birth has been touted as a method of sex selection by various birth calendars with controversial results. It is made to believe that indeed there is a relation of lunar phase at the time of conception/intercourse which results in birth of a particular gender. The purpose of this study was to examine the influence of the lunar phase on the possible relationship between lunar position at EDD/LMP and the gender of the child. Methods: One thousand and five deliveries were retrospectively analysed from 1 January 2016 to 31 December 2018 at the department of obstetrics and gynaecology of military hospital, Gwalior (latitude and longitude coordinates: 26.218287, 78.182831). Females having regular menstrual periods history around conception and in general their periods have been normal and regular were included in the study. Females having irregular menstrual periods history or having oligomenorrhoea/polymenorrhoea, ART/IVF conceptions were excluded from the study. Exact lunar phases were determined at the time of EDD and not with their LMP since that would automatically corelate well with LMP because of regularity of their periods. The actual date of birth was not considered while corelating with moon phase because of obvious reason of unexpected timing of labour. Results: The analysis revealed no significant correlation of gender of the child to lunar phases at EDD. This would indirectly corelate well with the LMP since the inclusion criterion had females having normal and regular menstrual periods. Conclusions: There is no predictable influence of the lunar phase on the gender of the baby. As expected, and in agreement with some recent studies this pervasive myth is not evidence based.